2022
DOI: 10.3390/polym14030413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3D-Printed PLA Structure on Sound Reflection Properties

Abstract: 3D printing technique is currently one of the promising emerging technologies. It is used in many areas of human activity, including acoustic applications. This paper focuses on studying the sound reflection behavior of four different types of 3D-printed open-porous polylactic acid (PLA) material structures, namely cartesian, octagonal, rhomboid and starlit structures. Sound reflection properties were evaluated by means of the normal incidence sound reflection coefficient based on the transfer function method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…For 3D-printed parts, the additive manufacturing process typically produces rougher, more uneven surfaces due to the accumulation of small errors and irregularities between layers over a vertical distance. This surface defect, in turn, impacts the acoustic properties from the experiment [ 49 , 50 ]. However, this analysis remains valid for studying the characteristics of tunneling frequencies in broadband stopbands.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…For 3D-printed parts, the additive manufacturing process typically produces rougher, more uneven surfaces due to the accumulation of small errors and irregularities between layers over a vertical distance. This surface defect, in turn, impacts the acoustic properties from the experiment [ 49 , 50 ]. However, this analysis remains valid for studying the characteristics of tunneling frequencies in broadband stopbands.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Monkova et al [33] found that the reflective properties of PLA samples were influenced not only by the type of structure but also by the porosity and thickness of the samples. In a recent study [34], the influence of arbitrarily varying cross-sectional perforations on the acoustic behavior of 3D-printed PLA parts with a divergent-convergent pattern was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The sound reflection coefficient (β) measures the vertical propagation of sound waves through 3D-printed samples [33] by using the impedance tube method. A summary of the sound absorption coefficient results is presented as follows: the highest values for the 0.8 mm nozzle diameter were obtained with the Black PLA Pro material; for the 0.6 mm diameter nozzle, the highest values of β were attributed to the Natural PLA material; for the 0.4 mm diameter nozzle, the maximum values were very close (exceeding 0.9), and each material had two maximum values.…”
mentioning
confidence: 99%
“…Specifically, the use of intelligent algorithms, such as Artificial Neural Network (ANN) [20], [21], and other time-domain feature extraction [22] methods based on sound and vibration patterns during printing, have shown promise in detecting and predicting conditions within the printing machines. By recording data with sensors [23] within a soundproof room [24], the ANN can anticipate future signals and vibrations, thereby identifying print results and avoiding filament damage. In conclusion, the integration of machine learning techniques [17] into 3D printing monitoring systems has the potential to significantly improve the reliability, efficiency, and quality of the additive manufacturing process [25].…”
Section: Introductionmentioning
confidence: 99%